2019
DOI: 10.4103/lungindia.lungindia_129_18
|View full text |Cite
|
Sign up to set email alerts
|

Burden of obstructive lung disease study in Iran: First report of the prevalence and risk factors of copd in five provinces

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a global health burden that affects 300 million people worldwide. Globally, COPD was reported as the fourth leading cause of death in 2004 and is projected to occupy the third position in 2030. The goal of the present project is to describe the prevalence and determine the causes and risk factors of COPD in five provinces of Iran. Methods: This study followed a stratified cluster sampling strategy with proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In another study conducted in five different geographical areas in Iran (north, south, west, and east of Iran), the overall prevalence of COPD was estimated at 4.9%. The prevalence of COPD was 2.8% in Mashhad, 3.7% in Mazandaran, 8.8% in Ahvaz, 4.1% in Tehran, and 13.9% in Kerman 26 . The prevalence of COPD was higher in our study than in the BOLD study including 14 countries, which reported the prevalence of COPD grade 2 to be over 1.8% 27 .…”
Section: Discussionmentioning
confidence: 94%
“…In another study conducted in five different geographical areas in Iran (north, south, west, and east of Iran), the overall prevalence of COPD was estimated at 4.9%. The prevalence of COPD was 2.8% in Mashhad, 3.7% in Mazandaran, 8.8% in Ahvaz, 4.1% in Tehran, and 13.9% in Kerman 26 . The prevalence of COPD was higher in our study than in the BOLD study including 14 countries, which reported the prevalence of COPD grade 2 to be over 1.8% 27 .…”
Section: Discussionmentioning
confidence: 94%
“…1 It is estimated that COPD will be the fourth leading cause of death in 2030 worldwide, a 1-step move up in the rank order compared with 2002. 2 The prevalence of the disease was reported to be 4.9% in Iran 3 and 9.2% in Tehran. 4 It was also demonstrated that patients with COPD have 50% lower long-term survival compared with their healthy counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…These cohort studies, however, did find that COPD patients had a worse prognosis for severe and fatal COVID-19 [22] , [23] , [24] , [25] , [26] , [27] . For reference, the COPD prevalence in the adult general population is 13-15% in South Korea [28] , [29] , 8% in Mexico [30] , 10% in Spain [31] , 5% in Iran [32] , and 7% in Kuwait [33] .…”
Section: Introductionmentioning
confidence: 99%